MEANING OF ILLNESS TINJAUAN KOMUNIKASI KESEHATAN DALAM PERSPEKTIF ISLAM - Rahmawati, Pudji; Muljohardjono, Hanafi (Jurnal Komunikasi Islam, 2016)
Understanding the sick (meaning of illness) is an important part in the healing process. Conceiving the meaning of pain or any illness is the result of an interpretation process that generates the meaning of illness. Pain, which could be interpreted both positively and negatively by the patients, generally comes from knowledge and experience of interacting with illnesses, diseases, medicines and the environment. The meaning of pain in the health communication perspective is a form of intrapersonal communication related to health. The role of health intrapersonal communication is very important, especially for understanding the meaning of pain that turns an impact on a person's physical condition. The meaning of pain in the Islamic perspective could demonstrate that pain is interpreted as a test as well as a proof that Allah will always wish the kindness for all His creatures